Expanding the Use of Molten Salt for Renewable Energy Storage and the Role of Green Technology Policies - Lavinia Heisenberg; Richhild Moessner (CESifo GmbH, 2024)
The transition to net zero carbon emissions necessary to limit global warming importantly involves greater use of renewable energies, especially solar energy, and scaling up renewable energy storage and generation. This paper discusses expanding the use of molten salt for renewable energy storage and generation, in an environmentally friendly way and making use of existing infrastructure. This includes using molten salt to store solar energy in concentrated solar plants, replacing coal by molten salt to power thermal plants and thereby convert existing coal thermal plants to renewables, and linking these two uses. Additionally, the use of molten salt in thermal batteries for grid-scale energy storage and in green hydrogen production is explored. The paper also delves into the significance of green technology policies in facilitating the use of molten salt for these applications.
Keywords: Q00; Q48; Q58; Q40; Q50; Q55; 330; molten salt; energy storage; renewable energy; solar energy; concentrated solar power plants; grid storage; conversion of thermal coal plants; green technology support policies